If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 9) = 8(x + -1) Reorder the terms: 7(9 + x) = 8(x + -1) (9 * 7 + x * 7) = 8(x + -1) (63 + 7x) = 8(x + -1) Reorder the terms: 63 + 7x = 8(-1 + x) 63 + 7x = (-1 * 8 + x * 8) 63 + 7x = (-8 + 8x) Solving 63 + 7x = -8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 63 + 7x + -8x = -8 + 8x + -8x Combine like terms: 7x + -8x = -1x 63 + -1x = -8 + 8x + -8x Combine like terms: 8x + -8x = 0 63 + -1x = -8 + 0 63 + -1x = -8 Add '-63' to each side of the equation. 63 + -63 + -1x = -8 + -63 Combine like terms: 63 + -63 = 0 0 + -1x = -8 + -63 -1x = -8 + -63 Combine like terms: -8 + -63 = -71 -1x = -71 Divide each side by '-1'. x = 71 Simplifying x = 71
| -3a^-2b^3/15a^-7b^-1 | | 33x^2-32x-585=0 | | -4(6y-6)-y=-4(y-5) | | b/8+1/3=19 | | f(x)=3(2+2)-4 | | 4(2-(1/8)p)=(1/4)p-7 | | x^2-10x+21=(x-7)(x+3) | | 6n+6/9=12 | | 3x-5+7=2x-9 | | 15s^2-8s+1=0 | | 9x+5(35-x)=287 | | 6(3x+1)=3x-9X | | 1/4x+4=y | | y^3=-21 | | -12x+2(x-5)+9x=3x-10 | | x+y=15andx-2 | | -3.5=x/7 | | 8b-9y/4b-b-5y/4b | | b-9y/4b-b-5y/4b | | 8b-9y/4b-b-5y/4b=0 | | 2x^3-1-1=0 | | 20+3m+6m=92 | | -52^1/2 | | 11/2d=8 | | 1/5(10x-4)=7 | | -11/2d | | (4x+15)+(-5+2x)+(-10+6x)=360 | | 144/2 | | -[6z-(17z+9)]=9+(10z+1) | | 0=24x^3+20x^2-54x-45 | | 10+25=-5(9x-7) | | 2x-8y-9x+6y= |